Information practices in a city of intermediate scale: sadness, social networks and incidental consumption - Heram, Yamila (2024)
The objective of this paper is to investigate the information practices of the urban population of Las Flores, province of Buenos Aires, Argentina. For this, an anonymous face-to-face survey developed by stratified ringing by census radio was carried out. The universe surveyed consisted of people between the ages of 18 and 79 residing in the town of Las Flores. The sample consisted of 260 cases controlled by gender, age and area quotas and is representative at the urban level of the municipality of Las Flores. The results indicate that the age variable can mainly explain the segmented information practices. The choice of social networks by young people and television by older adults. The local / national news variable predominates in terms of the type of support chosen to be informed. Incidental consumption stands out in young people and the feeling of sadness regarding the news is transversal to the entire population, differentiating local news from national/international news.